School skeleton by Ron Roy; illustrated by John Steven Gurney - Roy, ROn; Gurney, John, ill (New York Random House, 2003)
At Green Lawn Elementary, the entire school becomes involved in a mystery when Mr. Bones, the skeleton in the nurse's office, disappears.
A Stepping Stone book.
Keywords: Skeleton-Fiction; Lost and found possessions-Fiction; Schools-Fiction; April Fools' day-Fiction; Mystery and detective stories